TEACHING PROPORTIONALITY: TEACHERS' CONCEPTIONS AND REPORTED PRACTICES - Laëtitia DRAGONE (Universitaria Publishing House, Craiova, 2022)
Proportionality in mathematics occupies an important place not only in teaching but also in everyday life. Roblin (2015) tells us that it is not an easy thing to teach. This article aims to understand teachers' teaching methods in proportionality. To achieve this, a questionnaire distributed to primary and secondary school teachers will allow us to analyze their conceptions and their declared practices when teaching proportionality and this, according to their level of teaching: primary or secondary. Our results show that the level of difficulty of teaching proportionality perceived by the teachers is high. Our analyses will be followed by a discussion and recommendations for the training and teaching of proportionality.